Study of developmental genes in opisthosomal limb development in the spider Parasteatoda tepidariorum - Gaspar, Miguel Anthony Grilo, 1989- (2012)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2012